Environmental Management and Power Generation in Czech Republic - ANTOŠOVÁ, Gabriela (Journal of Environmental Management and Tourism, 2025)
Purpose : This article emphasizes the urgent claim for a sustainable approach embedded in the efforts of economic theory for spurring long run growth. The recent approach in the field of economic modelling and climate change estimates the impacts of unfettered economic activity on the atmosphere and on the climate. In such terms, this article presents the most relevant findings linking sustainability and economic growth in order to encompass the current situation of the Czech power generation sector. Methodology : A descriptive narrative intended to unfold the main theoretical developments of economic theory and climate change based on the contribution of the 2018 Nobel Prize Nordhaus and the main results of the climate change modelling. There, the emphasis marks the interaction between technological change and the preservation of natural resources, encompassed in an international effort for engaging the main contaminant countries in an effort of abatement. This theoretical bedrock provides us with the set of criteria to assess the method and the technology for generating power in the Czech Republic in a sustainable way. Findings : The blatant threat coming from global warming and climate change requires the involvement of the most contaminant countries. The article demonstrates that a game based on non-cooperative rules is not an incentive for complying the environmental goals. With no effective sanctions for the contaminant countries there is no incentive to comply with the rules. From the point of the economic theory, the first step for punishing the carbon emissions and contamination is the assignment of an economic value to the emissions, and to the extent that it makes up a negative externality, the contaminant agent must pay a cost due to an unsustainable production process and technology. Originality : The new sectorial and macroeconomic approaches involve the participation of private sector, the government and supranational spheres for ruling and implementing sustainable production practices and goals. Europe has been an example of concern for the definition of ambitious environmental goals, and the Czech Republic echoes the collective guidelines intended to make the economy more environmentally friendly.